The Effectiveness of a Literacy-Based Pop-Up Book Learning Model in Indonesian Language Learning for Elementary School Students: Systematic Literature Review - Pungut Pitaloka; Yasinta Mahendra (Journal for Lesson and Learning Studies, 2025)
The low literacy skills of elementary school students remain a challenge in Indonesian language learning, as many students still face difficulties in reading, writing, and storytelling. This situation requires innovative learning media that can foster motivation, engagement, and meaningful learning experiences. This study aims to analyze and synthesize the effectiveness of a literacy-based pop-up book learning model in Indonesian language learning through a systematic literature review (SLR). We examined and selected eight peer-reviewed articles published between 2020 and 2025 using predetermined inclusion and exclusion criteria through Google Scholar. We systematically extracted the data and thematically analyzed it to identify patterns of effectiveness, implementation strategies, and challenges. The findings reveal that pop-up book media significantly enhance literacy skills, particularly reading comprehension, creative writing, and oral storytelling, while simultaneously strengthening student motivation and participation through engaging visual representations. Moreover, the integration of pop-up books with interactive learning strategies such as quantum teaching demonstrates a higher impact on learning outcomes. Nevertheless, constraints related to teacher competence and resource availability remain obstacles to broader implementation. This study concludes that pop-up books are an effective medium for promoting literacy-based learning in elementary education and recommends continuous innovation supported by policy and teacher professional development to ensure sustainability and scalability.